Addressing inequities in the otolaryngology academic publishing: A call to action - Sarah Nuss; Rolvix H. Patterson; Mary J. Xu; Amina Seguya; Valerie Salano; Nader Zalaquett; Samuel Okerosi; Bethany Hedt-Gauthier; Johannes Fagan (Journal of the Colleges of Medicine of South Africa)
Article processing charges (APCs) for open access (OA) journals perpetuate inequities in scientific knowledge. High APCs systematically restrict low- and middle-income country (LMIC) researchers from contributing to research knowledge, preventing the dissemination of high-value, high-quality, and sustainable LMIC-driven solutions. Otolaryngology journals are no exception. The authors propose solutions to rectify the inequities in academic publishing because of APCs, including innovative solutions adopted by several major journals. Addressing these inequities requires medical society and journal editorial board leadership to ensure equitable APC policies.